Interfacial improvement of carbon fiber/epoxy composites using one-step method for grafting carbon nanotubes on the fibers at ultra-low temperatures - Yao, Zhiqiang; Wang, Chengguo; Qin, Jianjie; Su, Shunsheng; Wang, Yanxiang; Wang, Qifen; Yu, Meijie; Wei, Huazhen (Carbon (New York), 2020)
This paper focuses on improving the out-of-plane properties of carbon fiber/epoxy composites to extend their applications. Carbon nanotubes (CNTs) were introduced on carbon fiber surface by a novel one-step chemical vapor deposition (CVD) method at ultra-low temperature and hybrid composites were fabricated by molding technology. Mechanical and dielectric tests were conducted to figure out the changes in out-of-plane properties after grafting CNTs. The results of single-fiber tensile strength indicated that both the strength and the Weibull modulus of the CNTs-coated carbon fiber increased due to the less damage caused to the fiber by catalysts at low temperature and the repairing effect of the CNTs. Compared with the properties of desized fiber based composites, both interfacial shear strength (IFSS) and interlaminar shear strength (ILSS) of CNTs-coated fiber/epoxy composites increased by 30.73% and 32.29%, respectively, as well as the dielectric properties were also improved. The fracture mechanisms of CNTs were investigated based on the morphology observation on the interface. The improved out-of-plane properties were associated with the improved stress transfer between the carbon fibers and surrounding matrix through the newly formed interphase induced by CNT layer. TEM images of the structure of CNTs.The fracture surface in the weft direction of CNTs-coated carbon fiber/epoxy composites. [Display omitted]